TRANSFORMASI KURIKULUM PENDIDIKAN ISLAM DI ERA GLOBALISASI - Ahmad Khori; Rikha Destya Rahmadanti; Rizki Akbar Mubaroq Azhar; Rosmayati (STKIP Subang, 2026)
This study aims to analyze the transformation of the Islamic education curriculum in the era of globalization by highlighting the dynamics between adaptation and assimilation of Islamic values. Globalization, characterized by technological developments, information flows, and cross-cultural interactions, demands that Islamic education adapt without losing its identity. This study uses a qualitative approach with library research through analysis of various relevant scientific literature. The results indicate that the transformation of the Islamic education curriculum is influenced by internal factors such as limited human resources and weak integration of Islamic values, as well as external factors such as globalization, digitalization, and the demands of the global job market. The impact of the transformation is seen in changes in students' mindsets, challenges in national curriculum integration, and opportunities for the internationalization of Islamic education. This study proposes the Integrative-Adaptive Islamic Curriculum (IAIC) model as a strategic solution that integrates Islamic values ​​with global competencies in a balanced manner. This model is expected to maintain the identity of Islamic education while increasing global competitiveness. Keywords: Curriculum Transformation, Islamic Education, Globalization, Adaptation, Assimilation.